The Correlation Between Studentsâ€™ Emotional Quotient(EQ), Intelligence Quotient (IQ) and Their Vocabulary Knowledge in Second Grade of SMA Negeri 2 Kendari - Lukman, Arfina; Siam, Siam (Universitas Halu Oleo, 2021)
This study is conducted to know whether there is a significant correlation among studentsâ€™ Emotional Quotient (EQ), Intelligence Quotient (IQ), and vocabulary knowledge. This study was a correlational design which employed quantitative research methods. The sample of this study was 34 students which were from XI MIPA 1 in SMAN 2 Kendari. The sampling was taken by random sampling technique. The researcher used 3 instruments such as EQ questionnaire, RPMâ€™s IQ test, and the New Vocabulary Level Test (NVLT) to collect the data. Then the data were analyzed by using Pearson product-moment through SPSS 16.0. The result shows that the coefficient correlation between studentsâ€™ EQ and their vocabulary knowledge (r=0.482) that indicates a significant correlation and also the coefficient correlation between studentsâ€™ IQ and their vocabulary knowledge (r=0.437) also indicates there is a significant correlation. The significant score of each studentsâ€™ EQ and IQ has a significant correlation with vocabulary knowledge because its probability value (sig.2- tailed) is 0.004 and 0.010 which lower than 0.05 (sig (2-tailed) < âˆ). It can be concluded that H1 is accepted and H0 is unaccepted. This indicates that there is a significant correlation between studentsâ€™ EQ and their vocabulary knowledge and also there is a significant correlation between studentsâ€™ IQ and their vocabulary knowledge.